Uncovering Performance Differences in Backbone ISPs with Netdiff - Mahajan, Ratul; Zhang, Ming; Poole, Lindsey; Pai, Vivek (NSDI, 2008)
We design and implement Netdiff, a system that enables detailed performance comparisons among ISP networks. It helps customers and applications determine, for instance, which ISP offers the best performance for their specific workload. Netdiff is easy to deploy because it requires only a modest number of nodes and does not require active cooperation from ISPs. Realizing such a system, however, is challenging as we must aggressively reduce probing cost and ensure that the results are robust to measurement noise. We describe the techniques that Netdiff uses to address these challenges. Netdiff has been measuring eighteen backbone ISPs since February 2007. Its techniques allow it to capture an accurate view of an ISP’s performance in terms of latency within fifteen minutes. Using Netdiff, we find that the relative performance of ISPs depends on many factors, including the geographic properties of traffic and the popularity of destinations. Thus, the detailed comparison that Netdiff provides is important for identifying ISPs that perform well for a given workload.